Analysis of recycled rubber: Development of an analytical method and determination of polycyclic aromatic hydrocarbons and heterocyclic aromatic compounds in rubber matrices. (August 2021) - Skoczyńska, Ewa; Leonards, Pim E.G.; Llompart, Maria; de Boer, Jacob
Abstract: Recycled crumb rubber (CR) is rich in compounds with unrecognized toxic potency; this study aims at the development of an analytical method that would allow identification and quantification of a very wide range of organic compounds extractable from the complex rubber matrix. The analytical set-up includes target analysis of polycyclic aromatic hydrocarbons (PAHs) and methyl-PAHs and suspect screening of raw extracts to tentatively identify primary organic compounds present, but not included in the standard target analysis of recycled rubber, followed by analytical method development and target analysis of identified compounds. Analyzed samples included weathered and new CR originating from football turf granulates, rubber mats, and end-of-life car tires (ELTs). The developed analytical method involves sonication extraction, followed by solid phase extraction (SPE) fractionation that enables simple and efficient separation of analytes with broad polarity scale. The application of SPE fractionation resolves coelution problems and simplifies the chromatograms. This analytical approach allowed to identify and quantify 46 sample specific compounds, including several heterocyclic PAHs like 2-methylthiobenzothiazole, benzonapthothiophenes, benzonaphthofuranes and aromatic amines like diphenylamine and N-phenyl-2-naphthylamine, which to our knowledge were not determined before. The PAHs concentrations determined in CR tiles purchased in Dutch and Spanish shops exceed the EU limits for articles marketed for use by the public. Furthermore, sets of methylated PAHs, dibenzothiazoles and aromatic amines were identified and quantified, and several other compounds were tentatively identified. The obtained results stress the need for expanding the list of target compounds analyzed in CR and the need for longitudinal studies on weathering processes taking place in CR. Highlights: The presented method gave the best results for analysis of a wide suite of aromatic compounds present in crumb rubber. Identification of 21 heterocyclic compounds, two aromatic amines and several methyl-PAHs together with the 16 EPA PAHs. Mats purchased in Dutch shops exceed the EU limits for articles placed on the market for use by the public. The obtained results stress the need for expanding the list of target compounds analyzed in crumb rubber.